2024
DOI: 10.3390/ani14040541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Chitosan on the Muscle Composition, Digestion, Lipid Metabolism, and Stress Resistance of Juvenile Tilapia (Oreochromis niloticus) Exposed to Cadmium-Induced Stress

Qin Zhang,
Yi Xie,
Yuanhui Zhang
et al.

Abstract: The aim of this study was to investigate the effects of dietary chitosan supplementation on the muscle composition, digestion, lipid metabolism, and stress resistance, and their related gene expression, of juvenile tilapia (Oreochromis niloticus) subjected to cadmium (Cd2+) stress. Juvenile tilapia with an initial body weight of 21.21 ± 0.24 g were fed with a formulated feed containing five different levels (0%, 0.5%, 1.0%, 1.5%, and 2.0%) of chitosan for 60 days, while the water in all experimental groups con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Concomitantly, CdCl 2 enhanced the TC and TG levels, were accompanied by lipid accumulation in the serum and liver of rats. Besides, it also upregulated the mRNA and protein levels of FAS, SREBP1, and SREBP2 but downregulated CPT1, PPAR, and CPT2 mRNA levels ( Zhang et al, 2024 ). Hence, in our experiment, it was found that ATGL, CPT1, PPAR, MCAD, and LCAD mRNA transcriptional levels in the Cd group were dramatically downregulated compared with the control group, and FAS, SREBP1, and CPT2 mRNA transcriptional levels were observably upregulated in Cd group.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, CdCl 2 enhanced the TC and TG levels, were accompanied by lipid accumulation in the serum and liver of rats. Besides, it also upregulated the mRNA and protein levels of FAS, SREBP1, and SREBP2 but downregulated CPT1, PPAR, and CPT2 mRNA levels ( Zhang et al, 2024 ). Hence, in our experiment, it was found that ATGL, CPT1, PPAR, MCAD, and LCAD mRNA transcriptional levels in the Cd group were dramatically downregulated compared with the control group, and FAS, SREBP1, and CPT2 mRNA transcriptional levels were observably upregulated in Cd group.…”
Section: Discussionmentioning
confidence: 99%